Antifungal agents, yeast abundance and diversity in surface water: Potential risks to water users - Monapathi, Mzimkhulu; Horn, Suranie; Vogt, Tash; van Wyk, Deidré; Mienie, Charlotte; Ezeokoli, Obinna T.; Coertze, Roelof; Rhode, Owen; Bezuidenhout, Cornelius C. (Chemosphere (Oxford), 2021)
South African surface waters are subject to various forms of pollution. Recent findings in aquatic systems suggest an association exists between yeast diversity, chemical pollutants and land coverage, which are important water quality determinants. Yeast abundance and diversity, as well as antifungal agents in two river systems in South Africa, were investigated and related to the existing land coverage. Yeast abundance and diversity were determined from environmental DNA by quantitative polymerase chain reaction and next-generation sequencing, respectively, of the 26S ribosomal ribonucleic acid (rRNA) gene. Antifungal agents were qualitatively and/or quantitatively detected by ultra-high-pressure liquid chromatography-mass spectrometry. Analyses of 2 031 714 high-quality 26S rRNA sequences yielded 5554 amplicon sequence variants (ASVs)/species. ASV richness and Shannon-Wiener index of diversity reflected the southward flow of the river with higher values observed downstream compared to the upstream. Fluconazole concentrations were quantifiable in only two samples; 178 and 271 ng L−1. Taxonomically, at least 20 yeast species were detected, including the dominant Candida tropicalis, Cryptococcus spp. as well as the lesser dominant Bensingtonia bomiensis, Fereydounia khargensis, Hericium erinaceus, Kondoa changbaiensi, Pseudozyma spp. and Sphacelotheca pamparum. The two dominant species are known opportunistic pathogens which had antifungal resistant traits in previous studies from the same rivers and therefore is a public health threat. The present study provides further evidence that yeasts should be included as part of water quality parameters, especially in developing countries where much of the population are economically disadvantaged, and also immunocompromised due to age and disease. •Diversity, abundance of yeast and antifungals determined via NGS, qPCR and UHPLC-MS.•Candida tropicalis, a potential pathogen, was relatively most dominant.•Fluconazole concentration was positively correlated to mining and urban activities.•Correlation between C. tropicalis and fluconazole suggest fluconazole-resistance.